637. Β-Lactam (BL) Antibiotics Promote an IL-1β Response in Patients with Staphylococcus aureus Bacteremia (SaB). (26th November 2018) - Volk, Cecilia; Edwardson, Graham; Nizet, Victor; Sakoulas, George; Rose, Warren
Abstract: Background: BL therapy has been associated with reduced SaB duration compared with non-BL therapy. It has been shown that patients with SaB who fail to generate increased serum IL-1β are at risk for prolonged SaB (> 4 days duration), a predictor of mortality. This suggests a major role for the IL-1β host response in prompt clearance of SaB. Furthermore, BL result in reduced peptidoglycan cross-linking, reduced peptidoglycan O-acetylation, and increased alpha-toxin expression, all of which have independently been shown to enhance IL-1β release. This study aims to show that BL therapy results in a more robust IL-1β host response compared with non-BL therapy to explain, in part, more rapid SaB clearance. Methods: Fifty-nine patients (47 MRSA and 12 MSSA) with diverse SaB sources, including endovascular, extravascular (e.g., pneumonia), and catheter-related infections were included. In the first 48 hours, patients were treated with either BL, including oxacillin, ceftaroline, or cefazolin ( n = 24), vs. non-BL vancomycin or daptomycin ( n = 35). IL-1β concentrations were determined by ELISA on serum samples obtained on Days 1, 3 and Day 7 after bacteremia onset and compared between groups by Mann–Whitney U test. Results: Patients in BL and non-BL groups had similar IL-1β concentrations on Day 1 of bacteremia (median BL 6.1 pg/mL vs. non-BL 2.8 pg/mL, P = 0.090). BL-treated patients had significantly higher IL-1β serum concentrations on Day 3 (median 7.54 mg/mL vs. 1.9 pg/mL; P = 0.007) and Day 7 (12.52 pg/mL vs. 1.56 pg/mL, P = 0.016) when compared with non-BL-treated patients. BL therapy resulted in 23% and 105% increase in IL-1β at Days 3 and 7, respectively, while non-BL treatment resulted in 32% and 44% reduction in IL-1β. The median duration of SaB was similar between BL and non-BL-treated patients (2.5 vs. 2.0 days, respectively, P = 0.590). Conclusion: Given that a lack of inflammasome-mediated IL-1β production is associated with prolonged SaB, the significant increases in IL-1β levels in patients treated with BL has important therapeutic implications. Previously observed reduced duration of MRSA bacteremia with the addition of BL to vancomycin may have its basis on enhancing IL-1β release. A therapeutic regimen of vancomycin or daptomycin in combination with BL to treat MRSA bacteremia and use of BL therapy in MSSA bacteremia is strongly advised to improve outcomes based on these results. Disclosures: G. Sakoulas, Allergan: Consultant and Speaker, Consulting fee and Speaker honorarium. Sunovion: Speaker, Speaker honorarium. The Medicines Company: Speaker, Consulting fee. Paratek Pharmaceuticals: Consultant, Consulting fee. Cidara Therapeutics: Scientific Advisor, None. Arsanis Pharmaceuticals: Scientific Advisor, None. W. Rose, Merck: Grant Investigator, Research grant.